Indigenous Chicken production in Niger. (June 2019) - Moussa, H.O.; Keambou, T.C.; Hima, K.; Issa, S.; Motsa'a, S.J.; Bakasso, Y.
Abstract: The breeding of local chicken is an important source of animal protein and income for the rural populations of Niger, and the improvement of its productivity requires a better knowledge of production practices. Hence, a socio-economic and technical survey was undertaken from July to August 2017 in order to provide necessary information on the practice of family poultry keeping in Niger. For this purpose, two hundred and sixteen (216) producers were interviewed in the different agro-ecological zones of Niger using structured questionnaire. Results from the study revealed that 43.1% of local chicken producers are women. The most production purpose of the chicken in Niger is for selling (38.31%), self-consumption (37.74%) and donation (22.99%). Scavenging is the most dominant feeding system (92.1%). Constraints related to family poultry production as identified by the study are mainly diseases (45%), lack of housing (16%) which favors predation, lack of food (11%) and lack of training (8%). It is clear that the development of the sector necessarily involves strengthening the surveillance of avian diseases, coupled with veterinary monitoring and supervision of producers.